Outcomes of the Latarjet procedure for the treatment of chronic anterior shoulder instability: patients with prior arthroscopic Bankart repair versus primary cases. Issue 5 (31st May 2019) - Werthel, Jean-David; Sabatier, Vincent; Amsallem, Lior; Vigan, Marie; Hardy, Alexandre
Objectives: The two most common surgical interventions for recurrent anterior shoulder instability include arthroscopic Bankart repair and the Latarjet procedure. However, indications for each procedure remain debated between surgeons with 90% of surgeons (except French surgeons) preferring soft tissue Bankart repair initially. It remains unclear whether the results of a Latarjet procedure performed after a failed arthroscopic Bankart repair differ from those performed for primary cases. The purpose of our study was to compare the postoperative outcomes of patients who had undergone a Latarjet as a primary surgery versus those who had had a Latarjet as revision surgery for a failed arthroscopic Bankart repair Methods: Patients who had undergone open or arthroscopic Latarjet procedure between 2003 and 2015 in 5 fellowship-trained surgical practices were included. Charts were retrospectively reviewed to identify patients who had undergone a primary Latarjet or those who had had a Bankart repair prior to the Latarjet. Age, ISIS score, BMI, sports activity, hyperlaxity and delay before surgery were retrospectively collected. Outcome measures were prospectively collected, including range of motion, SSV, Walch-Duplay, scores, recurrence of instability, apprehension or new surgery. Results: A total of 311 patients were included. 28% of the patients were lost to follow-up and the mean follow-up was 3.4 years +/-0.8. There were 21 patients who had had a Bankart repair prior to the Latarjet procedure. Both populations were comparable regarding preoperative data. The postoperative instability rate was 3% in the overall population; 4.8% in the "primary Latarjet" group and 2.3% in the "Latarjet for failed Bankart" group. This difference was not significant (p=0.50). However, the mean Walch-Duplay score was significantly lower and the pain scores significantly higher in patients who had had a prior Bankart repair: 51.9 +/- 25 versus 72.1 +/- 25.2 and 2.5/10 versus 1.2/10 respectively. The Simple Shoulder Test was comparable in both groups. Conclusion: The study confirms that the Latarjet is an effective procedure to treat primary chronic anterior instability and also to stabilize a shoulder after a failed Bankart repair. However, the thought that a Bankart repair does not "burn any bridges" appears to be incorrect relative to postoperative pain and functional scores in the setting of future Latarjet procedure.